DIGITAL MARKETING DEVELOPMENT THROUGH INSTAGRAM: UPLIFTING MSMES TOWARDS - Fitri Dwiana; Ritha Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to reveal how digital marketing is implemented on Instagram to utilize technology on Instagram for MSMEs in Medan. The research method used in this research is a case study which is analyzed qualitatively. This research sampled the Woops.idn brand as an example of MSMEs in the city of Medan that have survived for more than 9 years and utilize social media Instagram as a marketing medium. In data collection, research produces and manages data in the form of interviews, field notes, images, photos, video recordings and so on. It can be seen that from 2015 until now, entrepreneurs use Instagram social media technology more often for their marketing than other forms of marketing to develop their own businesses.